2021
DOI: 10.1186/s43094-021-00204-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Antioxidant Analysis of Moringa oleifera Leaf Extracts from South Western States in Nigeria

Abstract: Background Moringa oleifera is a medicinal plant that ethnobotanical studies have shown its inclusion in treatment of many ailments such as diarrhea, diabetes, epilepsy, wound healing and arthritis. It is a plant that was believed to originate from India but could now be found in both the tropics and the sub-topics. Earlier reports have not addressed the association between the location of plant collection and its antioxidant contents. In this study, Moringa oleifera leaves were collected from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Phenolic acid and flavonoid compounds are known as potent radical scavengers and metals chelators (Ademosun et al, 2016). Olaoye et al (2021) reported on the total phenols, tannin, saponin, and flavonoids of moringa leaf leaves in‐vitro and its antioxidant activity on DPPH scavenging activity, nitric oxide scavenging activity, and lipid peroxidation reaction. Fruit peels of lemon, orange, and pomegranate are good sources of antioxidant polyphenols (Arora & Kaur, 2013) and Kopsell et al (2009) gives report of phenolic content to be present in maize.…”
Section: Resultsmentioning
confidence: 99%
“…Phenolic acid and flavonoid compounds are known as potent radical scavengers and metals chelators (Ademosun et al, 2016). Olaoye et al (2021) reported on the total phenols, tannin, saponin, and flavonoids of moringa leaf leaves in‐vitro and its antioxidant activity on DPPH scavenging activity, nitric oxide scavenging activity, and lipid peroxidation reaction. Fruit peels of lemon, orange, and pomegranate are good sources of antioxidant polyphenols (Arora & Kaur, 2013) and Kopsell et al (2009) gives report of phenolic content to be present in maize.…”
Section: Resultsmentioning
confidence: 99%
“…The antioxidant properties of Moringa were also greatly influenced by environmental parameters such as annual precipitation, minimum temperature, and maximum temperature on soil. Therefore, a recent study was conducted to determine the antioxidant properties of phenolic content in NP M. oleifera [ 103 ]. Therefore, studying the antioxidant capabilities of M. oleifera NPs produced using distinct extracts derived from different places is vital.…”
Section: Applications Of M Oleifera Npsmentioning
confidence: 99%
“…Since Metformin, a standard anti-diabetic drug employed in this study could not to protect against neuronal damage sufficiently similar to a precious report (Ekong et al 2022), it could be adduced that M. oleifera and V. amygdalina confer tissue protection by mechanism other than normalizing blood sugar. M. oleifera and V. amygdalina are rich sources of phenols, vitamins C and E which are well known antioxidants (Ganguly et al 2005;Olaoye et al 2021). This neuroprotective effect may be attributed to these antioxidants (Ekong et al 2017;Oladele et al 2020;Alara and Abdurahman 2021).…”
Section: Groupsmentioning
confidence: 99%
“…Moringa oleifera is used in folk medicine to treat diabetes (Dieye et al 2008;Nku-Ekpang et al 2015;Frederick et al 2020), as well as in the treatment of rheumatism, venom and microbial infections (Rajnish et al 2012). It is a rich source of antioxidant phytochemicals such as phenolic acids and flavonoids which play important roles in the defence against free radicals (Xu et al 2019;Olaoye et al 2021). It is believed that the antidiabetic properties of M. oleifera may be due its terpenoid constituents.…”
Section: Introductionmentioning
confidence: 99%